2012
DOI: 10.1542/peds.2011-2111
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Follow-up of Poor Inner-city Youth Between Ages 8 and 18: Intentions Versus Reality

Abstract: OBJECTIVES: (1) To document, at ages 8 to 10, children’s perceptions of their future and, at ages 16 to 18, youth outcomes; and (2) to assess early childhood factors associated with trajectory-altering events (TAEs), defined as youth risk behaviors that may modify developmental trajectories. METHODS: A prospective longitudinal study of 97 poor, inner-city, African American youth followed since birth who completed (1) early ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…10 Adherence is defined as the extent to which a person’s behavior corresponds with provider health recommendations. 11 While adherence rates vary among general pediatric populations, average adherence is 50%. 12 Studies of adherence in JIA have been limited, with most focusing on self- and parent-reported adherence, which tend to be inflated relative to more objective measures (e.g., electronic monitoring).…”
Section: Introductionmentioning
confidence: 99%
“…10 Adherence is defined as the extent to which a person’s behavior corresponds with provider health recommendations. 11 While adherence rates vary among general pediatric populations, average adherence is 50%. 12 Studies of adherence in JIA have been limited, with most focusing on self- and parent-reported adherence, which tend to be inflated relative to more objective measures (e.g., electronic monitoring).…”
Section: Introductionmentioning
confidence: 99%
“…While for many AYA, the life‐style balance sheet remains positive; this may not be the case for vulnerable groups including the homeless, the incarcerated, refugees and immigrants, rural and remote youth, AYA mothers and those with limited social competencies. The life trajectories for all these groups may be severely impaired with much of day to day living spent in survival mode . AYAM would have a great deal to offer these under‐served populations, who do not easily access traditional models of care.…”
Section: Life‐style Transitionsmentioning
confidence: 99%
“…The life trajectories for all these groups may be severely impaired with much of day to day living spent in survival mode. 37 AYAM would have a great deal to offer these under-served populations, who do not easily access traditional models of care.…”
Section: Life-style Transitionsmentioning
confidence: 99%
“…There is a remarkable dearth of research on healthcare communication during the transition from pediatric to adult care. For adolescent and young adult patients (AYAs), understanding the relative participation of conversation by all participants has the potential to promote successful transitions for AYAs with chronic health conditions [8].…”
Section: Introductionmentioning
confidence: 99%